Zimmermann's World resources and industries. - Zimmermann, Erich W.; Peach, W. Nelson; Constantin, James A. (New York: Harper & Row, 1972)
This is an important scholarly treatment of the world's resources in agriculture and industry, with a discussion of their relative importance and the degree and method of exploitation. A veritable mine of information.
Includes bibliographies.
sju 23/01/2019
Loans
Keywords: Natural resources; Industries; Agriculture; Economic geography